Alisamento capilar: de experimentos da ciência moderna ao design de objeto virtual de aprendizagem para a contextualização no ensino de Química - Lima, Thaís de Souza (2021)
For a long time, the addition of formaldehyde to cosmetic products by hairdressers with the purpose of hair straightening was common, due to its easy marketing. From 2009, aiming to restrain the indiscriminate use of formaldehyde added to hair products, due to its harmful effects to users, the Ministry of Health, through Anvisa, adopted the Board Collegiate Resolution – RDC 36, forbidding “the exposure, selling and delivering to consumers of formalin or formaldehyde (37% solution)” by stores, making it hard for hairdressers to add it to the products they sell. The improper continuity of this beautification practices, several questions were raised to Anvisa regarding the addition of formaldehyde to products of the cosmetics industry, leading it to adopt the 2013 Resolution 15, mandating a maximum percentile of 0,2% as a preservative. Given this scenario, the following questions are raised: if the use of formaldehyde is regulated by Anvisa, how come the substance is still used with concentrations above those allowed in beauty parlors? Which are the causes for the constant and improper usage of this substance? What is the necessary critical knowledge for society regarding the employment of this beautification practice? Based on advanced techniques of modern science (SEM, NMR and Identification and Quantification of Free Formaldehyde) to the analysis of hair strands and quantification of formaldehyde in cosmetics, this research aims at pointing to pedagogical elements that guide the teacher to provide a chemistry class with a focus on critical and reflexive formation of students in high school and university regarding the indiscriminate use of the practice of hair straightening, using as a mediating tool the virtual leaning objects (VLO) known as “Hair Straightening: under the microscopic eye”. Considering the researcher also works as a teacher and hair dresser, elements to analyze their own reality were sought in the participating research, aiming at the teaching of school concepts through the “hair straightening” theme. The stages of this investigation are: identifying the problem; elaborating a teaching and citizenship formation project; technical analysis of samples of products designed for hair straightening; elaboration of the VLO through the data obtained through the aforementioned techniques; theoretical considerations on the application of VLO in high school classes in Goiânia public schools. With the carrying out of this study, we expect to provide to the acting subjects with the knowledge to allow them to reflect critically about the relation between the consumption of beautification products and pratices and health and social well-being.